TECHNOLOGICAL PRINCIPLES FOR CREATING A SUIT THAT ENSURES HIGH RELIABILITY AND SAFETY IN AQUATIC ENVIRONMENTS - Mamaxanova, Zebuniso (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This article analyzes the technological foundations for creating a specialized suit that ensures high reliability and safety in aquatic environments. The study examines hydrodynamic conditions, the water resistance of materials, heat transfer, and compliance with ergonomic and biomechanical requirements. The rationale for applying functional zoning, a multilayer structure, and innovative sewing technologies in the suit’s construction is substantiated. Based on the research findings, scientific and practical recommendations have been developed for designing a high-performance and safe suit.